HUMANITIES EDUCATION AS A FACTOR OF ACMEOIOGICAL TRANSFORMATION OF THE FUTURE LAWYER’S PERSONAI CULTURE - Бовгиря, Дмитро (SWorldJournal, 2026)
The article explores the fundamental role of humanities training in the process of developing professionalism in future lawyers. In the context of Ukraine’s integration into the European legal space and the challenges of legal uncertainty, there is an ur